Application of Behavioral Norms Through Education Citizenship Based on Discovery Based Learning at Elementary School Level - Meisari, Rara (International Journal of Students Education, 2024)
Instilling behavioral norms at the elementary school level has an important role in forming the character of the younger generation with integrity and responsibility. Discovery-Based Learning (DBL)-based citizenship education offers an innovative approach to integrating norms into the learning process. Civic education will play a role in forming students who have a sense of nationality and love for their country and obey the rules that apply in society. Norm discipline in elementary school students is indeed very necessary, because norm discipline is included in the formation of character in children.This approach allows students to actively explore, understand, and apply these norms through a process of discovery and reflection. This research aims to explore the effectiveness of Discovery-Based Learning in instilling norm behavior in elementary school students. By using literature review and document analysis methods. The research results show that the DBL approach is able to increase students’ understanding of norms, strengthen their awareness of social responsibility, and build critical and creative thinking skills. Thus, applying this method can be a strategic solution in creating meaningful and relevant learning in citizenship education at the elementary school level.